2021
DOI: 10.3389/fimmu.2021.760999
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Differentiation-2 Protein Ameliorates DSS-Induced Ulcerative Colitis by Inhibiting NF-κB Activation in Neutrophils

Abstract: The loss of inhibitor of differentiation-2 (ID2) could lead to the development of colitis in mice, supplementation with exogenous ID2 protein might be a potential strategy to ameliorate colitis. In this study, the effects of ID2 protein supplementation on Dextran sodium sulfate (DSS)-induced colitis were investigated. Firstly, we confirmed that the expression of ID2 was reduced in the colon tissues of DSS-induced colitis mice and patients with ulcerative colitis (UC). Then, we constructed a recombinant plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In addition, a low-fat diet significantly reduced patients' levels of expressed inflammatory markers and attenuated the dysregulation of their gut microbiota. Studies based on IBD animal models have shown that proteolytic diets induce remission associated with decreased abundance of pathogens such as E. coli and Clostridium perfringens , increased abundance of Clostridium hiranonis , a secondary bile acid producer, and elevated levels of chicholic acid and deoxycholic acid[ 110 ].…”
Section: Aiec In Ucmentioning
confidence: 99%
“…In addition, a low-fat diet significantly reduced patients' levels of expressed inflammatory markers and attenuated the dysregulation of their gut microbiota. Studies based on IBD animal models have shown that proteolytic diets induce remission associated with decreased abundance of pathogens such as E. coli and Clostridium perfringens , increased abundance of Clostridium hiranonis , a secondary bile acid producer, and elevated levels of chicholic acid and deoxycholic acid[ 110 ].…”
Section: Aiec In Ucmentioning
confidence: 99%
“…This results in the main pathological feature of UC: chronic ulcerative damage to the colonic mucosa. Previous studies have confirmed the uncontrolled accumulation and persistence of PMNs in damaged mucosal lamina propria [11]. A vicious cycle is formed, in which infiltrating PMNs damage the mucosa, which in turn leads to further PMN infiltration.…”
Section: Introductionmentioning
confidence: 77%
“…At days 22 and 28, peripheral blood (PB) was collected from the mouse tail, and the absolute CD19 + NALM-6 numbers were determined using the flow cytometry with the 123count™ eBeads (Thermo Fisher, Cat#: 01–1234-42) as described in our previous study. 23 At day 35 after NALM-6 inoculation, the peripheral blood was collected from the mice, and the CD4 + and CD8 + subsets of T cells were counted with the 123count™ eBeads.…”
Section: Cytokine Assaymentioning
confidence: 99%